A High Performance Adaptive Digital LDO Regulator With Dithering and Dynamic Frequency Scaling for IoT Applications - Muhammad Asif; Imran Ali; Danial Khan; Muhammad Riaz Ur Rehman; Qurat- Ul-Ain; Muhammad Basim; Young Gun Pu; Minjae Lee; Keum Cheol Hwang; Youngoo Yang; Kang-Yoon Lee (IEEE Access)
In this paper, a high performance adaptive digital low-dropout voltage regulator (ADLDO) is proposed for Internet-of-Things (IoT) applications. In the proposed ADLDO, a fully synthesizable adaptive digital controller is designed. It automatically senses load variations and adaptively controls multi-loop architecture to reduce quiescent current, minimize output voltage ripples and achieve fast transient response. The multi-loop architecture with hill climbing reduces the total bi-directional shift registers length which results in the reduced leakage current in the transistor-switch-array (TSA), and improves the recovery time and output DC voltage accuracy. A dithering technique is introduced to eliminate the limit cycle oscillation (LCO) and improve the performance of the regulator. The dynamic frequency scaling (DFS) mechanism is proposed for reducing controller power consumption in steady state. In order to reduce the offset and output voltage error, a dynamic latch comparator is utilized. When the input supply voltage is varied from 0.5 V to 1 V, the measured output voltage ranges from 0.45 V to 0.95 V with 50 mV dropout voltage. The operating frequency is 10 MHz with fast transient response and quiescent current of 350 ns and $3.7~μ \text{A}$ , respectively. The maximum measured power and current efficiencies are 89.7 % and 99.97 %, respectively, with 1.9 mV output voltage ripples. Measured load and line regulations are 2.2 mV/mA and 9.5 mV/V respectively. The proposed circuit is implemented in 28 nm CMOS process and occupies 0.016 mm2 chip area.